A multiscale super-hydrophobic surface with light-heat performance and stability and a preparation method thereof

CN117926256BActive Publication Date: 2026-10-23CENT SOUTH UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410106185.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-25
Publication Date
2026-10-23
Estimated Expiration
2044-01-25

AI Technical Summary

Technical Problem

然而处于Wenzel状态的冰滴在融化后可能无法恢复为Cassie状态

Benefits of technology

[0022](1)本发明的上述方案首先通过刻蚀和原位氧化处理构建出微纳米分级结构,再旋涂TiN纳米颗粒制备出E/O@TiN,通过多尺度的表面结构、金属氧化物和TiN纳米颗粒的协同作用,使得E/O@TiN具有优异的超疏水性和光热性能,如E/O@TiN的接触角、滚动角和太阳光吸收率可分别达到163°±1.1°、2.5°±0.6°和0.925。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117926256B_ABST
    Figure CN117926256B_ABST
Patent Text Reader

Abstract

The application provides a multiscale super-hydrophobic surface with photo-thermal performance and stability and a preparation method thereof. The method successfully prepares a multiscale super-hydrophobic surface with photo-thermal performance and stability on a metal substrate through etching, in-situ oxidation and spin coating. The multiscale super-hydrophobic surface has excellent super-hydrophobicity and Cassie state stability. Meanwhile, due to the intrinsic high absorption performance of metal oxide and the plasmonic resonance of TiN nanoparticles, the E / O@TiN has a high solar absorption rate of 0.925. Under the illumination of one sun, an ice droplet can quickly slide off the E / O@TiN with a tilt of 7° in 121s; a 4mm-thick frost layer can be completely melted in 241s while the surface remains dry. The application simultaneously realizes the Cassie state stability in the ice melting process and excellent solar absorption performance, which is helpful for the practical development of photo-thermal super-hydrophobic surfaces in the application of ice prevention.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of coating materials technology, and in particular to a multi-scale superhydrophobic surface with both photothermal properties and stability, and its preparation method. Background Technology

[0002] Icing is a common natural phenomenon in low-temperature environments; when the temperature drops below 0°C, water freezes due to supercooling. For outdoor infrastructure such as cables, transportation equipment, and wind turbine blades, ice or frost accumulation can severely impact their operational efficiency and safety. Common de-icing methods include mechanical de-icing, chemical de-icing, electric heating de-icing, and electric pulse de-icing. However, these methods suffer from drawbacks such as high cost, energy consumption, and environmental pollution.

[0003] Inspired by the "lotus effect," superhydrophobic surfaces are considered to possess excellent anti-icing and de-icing properties due to their unique solid-liquid contact state, primarily manifested in dynamic de-icing, delayed icing, and reduced ice adhesion strength. However, icing is inevitable when the surface is exposed to low-temperature environments for extended periods. An effective solution is to combine photothermal effects with superhydrophobicity. By absorbing solar radiation to increase the surface temperature, anti-icing and de-icing properties are maintained at low temperatures, while the superhydrophobicity allows for rapid drainage of melted water to maintain photothermal properties.

[0004] However, most currently proposed photothermal superhydrophobic surfaces neglect the wettability transition of droplets during freezing and melting. In low-temperature and high-humidity environments, droplets inevitably penetrate the surface structure, transitioning from the Cassie state to the Wenzel state. However, ice droplets in the Wenzel state may not be able to revert to the Cassie state after melting. This interlocking contact state not only hinders the rapid sliding of molten droplets off the surface but also causes severe surface damage. Therefore, achieving Cassie state stability during the melting process is of great significance for improving the anti-icing and de-icing performance of photothermal superhydrophobic surfaces. Summary of the Invention

[0005] This invention provides a multi-scale superhydrophobic surface with both photothermal properties and stability, and a method for preparing the same, in order to solve the aforementioned problems in the prior art.

[0006] To achieve the above objectives, embodiments of the present invention provide a multi-scale superhydrophobic surface with both photothermal properties and stability, and a method for its preparation. This method successfully prepares a multi-scale superhydrophobic surface (E / O@TiN) with photothermal properties and stability on a metal substrate through etching, in-situ oxidation, and spin coating. This multi-scale superhydrophobic surface structure allows droplets to completely recover to their initial Cassie state after melting. Simultaneously, the intrinsic high absorption properties of the metal oxide and the plasmon resonance of the TiN nanoparticles result in E / O@TiN exhibiting a high solar absorptivity of 0.925. Due to its excellent superhydrophobicity and photothermal properties, under sunlight irradiation, ice droplets can rapidly slide off the 7° tilted E / O@TiN within 121 s; a 4 mm thick frost layer can completely melt in 241 s while the surface remains dry; and the freezing delay time can be extended from 21 s to 123 s. The present invention simultaneously achieves Cassie state stability during the melting process and excellent solar absorption performance, contributing to the practical development of photothermal superhydrophobic surfaces in anti-icing and de-icing applications.

[0007] Embodiments of the present invention provide a method for preparing a multi-scale superhydrophobic surface that combines photothermal properties and stability, comprising the following steps:

[0008] S1: Pretreatment of the metal substrate;

[0009] S2: The pretreated metal substrate is immersed in ferric chloride etching solution for chemical etching to obtain a surface with micron-sized dimensions;

[0010] S3: The micron-sized surface is transferred to a tube furnace and heated for in-situ oxidation. After in-situ oxidation, the alloy generates dense and uniform nanoscale metal oxides, thus forming a dual-scale structure surface with micro- and nano-scale dimensions. Simultaneously, the generated metal oxides exhibit high solar light absorption.

[0011] S4: The TiN solution is uniformly coated onto the multi-level structure surface with micro-nano scale by spin coating. After drying, a multi-scale superhydrophobic surface with both photothermal properties and stability is obtained, namely E / O@TiN.

[0012] Preferably, in step S1, the pretreatment process specifically includes polishing the metal substrate in 95% ethanol and ultrasonically cleaning it for 5 minutes, and then drying the surface of the metal substrate with a hair dryer.

[0013] Preferably, in step S1, the metal substrate comprises the following components by weight: Fe 67.5–74 wt.%, Cr 18–20 wt.%, Ni 8–10.5 wt.%, and Mn < 2.0 wt.%.

[0014] Preferably, in step S2, the ferric chloride etching solution is composed of 2 mol / L FeCl3, 37% HCl and 30% H2O2 mixed in a volume ratio of 15:1:1.

[0015] Preferably, in step S2, etching is performed at room temperature for 20–40 minutes.

[0016] Preferably, in step S3, the temperature is increased to 500-800°C at a heating rate of 600°C / h; the in-situ oxidation reaction time is 2h.

[0017] Preferably, the spin coating speed is 4000 rpm, the number of spin coatings is 3 to 7, the drying temperature is 90℃, and the drying time is 2 hours.

[0018] Preferably, in step S4, the TiN solution is prepared by mixing and stirring 2 wt.% of 20 nm TiN nanoparticles and 1 wt.% of 1H,1H,2H,2H-perfluorooctyltriethoxysilane in anhydrous ethanol.

[0019] Based on a general inventive concept, embodiments of the present invention provide a multi-scale superhydrophobic surface that combines photothermal properties and stability, obtained by the above-described preparation method.

[0020] Preferably, the multi-scale superhydrophobic surface has a contact angle (CA) as high as 163°, a roll-off angle (SA) as low as 2.5°, and a solar absorption rate of... Up to 0.925.

[0021] The above-described solution of the present invention has the following beneficial effects:

[0022] (1) The above-mentioned scheme of the present invention first constructs a micro-nano hierarchical structure through etching and in-situ oxidation treatment, and then spin-coates TiN nanoparticles to prepare E / O@TiN. Through the synergistic effect of multi-scale surface structure, metal oxide and TiN nanoparticles, E / O@TiN has excellent superhydrophobicity and photothermal properties. For example, the contact angle, roll-off angle and solar light absorption rate of E / O@TiN can reach 163°±1.1°, 2.5°±0.6° and 0.925, respectively.

[0023] (2) Compared to single-size and dual-scale superhydrophobic surfaces, E / O@TiN ensures more stable superhydrophobicity, and ice droplets can completely recover to the Cassie state after melting on the E / O@TiN surface. Due to the stability of the Cassie state during the melting process and the high solar absorption rate, E / O@TiN has excellent anti-icing and de-icing performance: under sunlight, ice droplets can quickly slide off the 7° tilted E / O@TiN within 121s, and a 4mm thick frost layer can completely melt and remain dry in 241s. In addition, the excellent superhydrophobicity effectively delays the frosting process, and the freezing delay time of droplets at -20℃ is extended from 21s to 123s.

[0024] (3) Compared with other methods for preparing photothermal superhydrophobic surfaces, such as laser etching and layer-by-layer deposition, this invention can quickly and cost-effectively prepare photothermal superhydrophobic surfaces on metal surfaces by chemical etching, in-situ oxidation and spin coating. At the same time, it achieves Cassie state stability and excellent solar absorption performance during the ice melting process, which is conducive to the practical development of photothermal superhydrophobic surfaces in anti-icing and de-icing applications. Attached Figure Description

[0025] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0026] Figure 1 This is a schematic flowchart of the preparation method of the multi-scale superhydrophobic surface E / O@TiN according to an embodiment of the present invention;

[0027] Figure 2 These are SEM images of the multi-scale superhydrophobic surface E / O@TiN after sequential etching, in-situ oxidation, and spin coating according to embodiments of the present invention.

[0028] Figure 3 These are physical images and contact angle diagrams of the multi-scale superhydrophobic surface E / O@TiN of Embodiment 1 of the present invention;

[0029] Figure 4 These are SEM images and contact angle diagrams of E@TiN prepared in Comparative Example 1 of this invention;

[0030] Figure 5 These are SEM images and contact angle diagrams of TiN prepared in Comparative Example 2 of this invention;

[0031] Figure 6The X-ray photoelectron spectra of 304 stainless steel after etching + in-situ oxidation treatment and etching + in-situ oxidation + spin coating treatment are shown in Example 3 of the present invention.

[0032] Figure 7 This invention presents the contact angle changes and images of test droplets during freezing and melting processes; wherein, Figure 7 (a) is Comparative Example 1. Figure 7 (b) is Comparative Example 2. Figure 7 (c) is Example 1;

[0033] Figure 8 These are the photothermal dynamic de-icing experiments of Example 1, Comparative Example 1, and Comparative Example 2 of this invention;

[0034] Figure 9 These are the photothermal defrosting tests of Example 1 and Comparative Example 2 in this invention.

[0035] Figure 10 This refers to the anti-icing test of 304 stainless steel, Comparative Example 1, Comparative Example 2, and Example 1 in this invention. Detailed Implementation

[0036] To make the technical problems, technical solutions and advantages of the present invention clearer, a detailed description will be given below in conjunction with the accompanying drawings and specific embodiments.

[0037] Unless otherwise defined, all technical terms used herein have the same meaning as commonly understood by those skilled in the art. The technical terms used herein are for the purpose of describing particular embodiments only and are not intended to limit the scope of the invention.

[0038] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0039] This invention addresses existing problems by providing a multi-scale superhydrophobic surface with both photothermal properties and stability, along with its preparation method. A schematic flowchart of the preparation method is shown below. Figure 1 As shown, the SEM images of the sample after sequential etching, in-situ oxidation, and spin coating are as follows: Figure 2 As shown.

[0040] The metal substrates in the following embodiments are all made of 304 stainless steel alloy with a thickness of 0.2 mm.

[0041] Example 1

[0042] A method for preparing a multi-scale superhydrophobic surface that combines photothermal properties and stability includes the following steps:

[0043] Step 1 Pretreatment: Polish and ultrasonically clean 304 stainless steel in 95% ethanol for 5 minutes, and then dry the surface with a hair dryer.

[0044] Step 2: Immerse 304 stainless steel in the etching solution at room temperature for 30 minutes. The etching solution consists of a mixture of 2 mol / L FeCl3, 37% HCl and 30% H2O2 (volume ratio 15:1:1).

[0045] Step 3: Transfer the etched sample to a tube furnace and heat it to 700°C at a heating rate of 600°C / h for in-situ oxidation. Hold the temperature for 2 hours, then cool it to 100°C in the furnace. Remove the sample and place it on a metal block to cool to room temperature.

[0046] Step 4: Spin-coat the TiN solution 5 times at 4000 rpm onto the oxidized sample surface. Finally, place the sample on a heating stage at 90℃ and dry for 2 hours to obtain E / O@TiN. The physical image and contact angle diagram of this multi-scale superhydrophobic surface E / O@TiN are shown below. Figure 3 As shown in the figure, the TiN solution was prepared by mixing and stirring 2 wt.% of 20 nm TiN nanoparticles and 1 wt.% of 1H,1H,2H,2H-perfluorooctyltriethoxysilane in anhydrous ethanol.

[0047] The sample obtained after the above treatment has a contact angle as high as 163°, a roll-off angle as low as 2.5°, and a solar absorptivity as high as 0.925.

[0048] Example 2

[0049] The difference between this embodiment and Embodiment 1 is that the etching time is adjusted to 40 minutes, while the other steps and parameters are the same as in Embodiment 1. The average contact angle, roll-off angle, and solar absorptivity are 162°, 3.2°, and 0.927, respectively.

[0050] Example 3

[0051] The difference between this embodiment and Embodiment 1 is that the number of spin coating cycles is adjusted to 7, while the other steps and parameters are the same as in Embodiment 1. The average contact angle, roll-off angle, and solar absorptivity are 161.7°, 2.6°, and 0.928, respectively.

[0052] Comparative Example 1

[0053] Only 304 stainless steel was etched and spin-coated (named E@TiN), i.e., step three of preparation example 1 was omitted. Its average contact angle, roll-off angle, and solar absorptivity were 151.2°, 30.2°, and 0.767, respectively. SEM images and contact angle diagrams are shown below. Figure 4 As shown.

[0054] Comparative Example 2

[0055] The preparation process of Comparative Example 2 includes the following steps:

[0056] Step 1 Pretreatment: Polish and ultrasonically clean 304 stainless steel in 95% ethanol for 5 minutes, and then dry the surface with a hair dryer.

[0057] Step 2: A TiN layer with a thickness of 800 μm is formed on the surface of 304 stainless steel using a TiN solution and an automatic coating machine, thus obtaining Comparative Example 2 (named TiN). The preparation process of the TiN solution is the same as in Example 1.

[0058] The average contact angle, roll-off angle, and solar absorptivity of Comparative Example 2 obtained by the above method were 155.0°, 9.7°, and 0.928, respectively. SEM images and contact angle diagrams are shown below. Figure 5 As shown.

[0059] Characterization of E / O@TiN:

[0060] from Figure 6 It can be seen that the untreated 304 stainless steel mainly exhibits Fe 2p, O 1s, and C 1s peaks, located at 711 eV, 530 eV, and 285 eV, respectively. After etching and in-situ oxidation treatment of the 304 stainless steel, the O 1s, Cr 2p, Ni 2p, and Fe 2p peaks can be observed more clearly, which is due to the formation of oxides after oxidation. After spin-coating with TiN solution, F 1s, Ti 2p, and N 1s peaks can be clearly observed on the sample surface, located at 688 eV, 459 eV, and 397 eV, respectively, indicating that E / O@TiN has been successfully prepared.

[0061] To better demonstrate the anti-icing and de-icing performance of E / O@TiN, comparative experiments were conducted using Example 1, 304 stainless steel, and Comparative Examples 1 and 2. Comparative Examples 1 and 2 correspond to photothermal superhydrophobic surfaces with dual and single feature scales, respectively. Specific experiments included the following:

[0062] (1) Icing and melting cycle test

[0063] like Figure 7 The freezing and melting processes of droplets on E@TiN, TiN, and E / O@TiN surfaces are illustrated. During freezing, the contact angle of the droplets on all three surfaces gradually decreases, while the contact area gradually increases. During melting, the contact angle of the droplets on the E / O@TiN surface recovers from 136.7° to 161.7°, while on the E@TiN and TiN surfaces, the contact angle only recovers to 138.1° and 145.5°, respectively. This indicates that E / O@TiN exhibits excellent Cassie stability during droplet melting.

[0064] (2) Dynamic photothermal de-icing test

[0065] like Figure 8 As shown, under 1x light intensity, ice droplets can rapidly roll off a 7° tilted E / O@TiN surface within 121 s without leaving any water droplets. For E@TiN and TiN surfaces, ice droplets begin to melt around 139 s and 90 s, respectively, and completely melt at 392 s and 249 s. However, the completely melted droplets cannot slide off the 10° tilted surface and remain adhered to it. The experimental environment was -20°C and 30% humidity.

[0066] (3) Photothermal defrosting test

[0067] like Figure 9 As shown, under 1x light intensity, a frost layer of approximately 4 mm can rapidly melt from the E / O@TiN surface within 241 s, and the surface remains dry throughout. For the TiN surface, melted water will remain on a large area of ​​the surface. The experimental environment was -20℃ and 30% humidity.

[0068] (4) Anti-icing test

[0069] like Figure 10 As shown, in a dark environment at -20°C, the freezing delay time of droplets on a 304 stainless steel surface is approximately 21 s. For E@TiN and TiN surfaces, the freezing delay times are 61 s and 108 s, respectively. However, droplets on the E / O@TiN surface become opaque at 89 seconds and do not freeze completely until 123 seconds. The freezing delay time of droplets on E / O@TiN is almost six times that of 304 stainless steel. The humidity of the experimental environment was 30%.

[0070] The above description represents the preferred embodiments of the present invention. It should be noted that those skilled in the art can make various improvements and modifications without departing from the principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a multi-scale superhydrophobic surface that combines photothermal properties and stability, characterized in that, Includes the following steps: S1: Pretreatment of the metal substrate; S2: The pretreated metal substrate is immersed in ferric chloride etching solution for chemical etching to obtain a surface with micron-sized surface; the ferric chloride etching solution is composed of 2 mol / L FeCl3, 37% HCl and 30% H2O2 mixed in a volume ratio of 15:1:1; etching is performed at room temperature for 20~40 min; S3: The surface with micron-sized dimensions is transferred to a tube furnace for in-situ oxidation treatment to obtain a dual-scale structure surface with micro- and nano-scale dimensions; the temperature is heated to 500~800℃ at a heating rate of 600℃ / h; the in-situ oxidation reaction time is 2h. S4: The TiN solution was uniformly coated onto the multi-level structured surface with micro- and nano-scale dimensions by spin coating. After drying, a multi-scale superhydrophobic surface with both photothermal properties and stability, namely E / O@TiN, was obtained. The spin coating speed was 4000 rpm, and the number of spin coatings was 3 to 7. The drying temperature was 90 °C, and the drying time was 2 h. The TiN solution was prepared by mixing and stirring 2 wt.% 20 nm TiN nanoparticles and 1 wt.% 1H,1H,2H,2H-perfluorooctyltriethoxysilane in anhydrous ethanol.

2. The method for preparing a multi-scale superhydrophobic surface with both photothermal properties and stability according to claim 1, characterized in that, In step S1, the pretreatment process specifically includes polishing the metal substrate in 95% ethanol and ultrasonically cleaning it for 5 minutes, and then drying the surface of the metal substrate with a hair dryer.

3. The method for preparing a multi-scale superhydrophobic surface with both photothermal properties and stability according to claim 1, characterized in that, In step S1, the metal substrate comprises the following components by weight: Fe 67.5~74 wt.%, Cr 18~20 wt.%, Ni 8~10.5 wt.% and Mn<2.0 wt.%.

4. The method for preparing a multi-scale superhydrophobic surface with both photothermal properties and stability according to claim 1, characterized in that, In step S4, the drying temperature is 90 °C and the drying time is 2 h.

5. A multi-scale superhydrophobic surface with both photothermal properties and stability obtained by the preparation method according to any one of claims 1 to 4.

6. A multi-scale superhydrophobic surface with both photothermal properties and stability according to claim 5, characterized in that, The multi-scale superhydrophobic surface has a contact angle as high as 163°, a roll-off angle as low as 2.5°, and a solar absorptivity as high as 0.925.

Citation Information

Patent Citations

  • Preparation method and application of novel super-hydrophobic photo-thermal MOF (Metal Organic Framework)-based surface with ice removing / preventing functions

    CN116515459A

  • Photothermal transducing particles, image forming material using the same and its production

    JP2001005177A